2019
DOI: 10.1056/nejmoa1908075
|View full text |Cite
|
Sign up to set email alerts
|

Encorafenib, Binimetinib, and Cetuximab in BRAF V600E–Mutated Colorectal Cancer

Abstract: Terms of use This work is brought to you by the University of Southern Denmark through the SDU Research Portal. Unless otherwise specified it has been shared according to the terms for self-archiving. If no other license is stated, these terms apply: • You may download this work for personal use only. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying this open access version T h e ne w e ngl a nd jou r na l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
800
4
23

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 1,126 publications
(917 citation statements)
references
References 34 publications
19
800
4
23
Order By: Relevance
“…In BRAF mutant melanoma and NSCLC, inhibition of two components of the same oncogenic pathway (BRAF+MEK, referred to as “vertical targeting”) has been shown to provide more lasting clinical benefit compared to inhibition of only BRAF 10, 11 . More recently, both clinical 12, 13 and pre-clinical 14 studies have shown that inhibition of three components of the same oncogenic pathway further increases therapeutic benefit. In these scenarios the drugs are used at maximum tolerated dose (MTD).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In BRAF mutant melanoma and NSCLC, inhibition of two components of the same oncogenic pathway (BRAF+MEK, referred to as “vertical targeting”) has been shown to provide more lasting clinical benefit compared to inhibition of only BRAF 10, 11 . More recently, both clinical 12, 13 and pre-clinical 14 studies have shown that inhibition of three components of the same oncogenic pathway further increases therapeutic benefit. In these scenarios the drugs are used at maximum tolerated dose (MTD).…”
mentioning
confidence: 99%
“…In the present MLD schedule, we target the MAPK pathway of the tumour itself, as growth inhibition in all cases parallels inhibition of the MAPK pathway (as judged by pRSK). Three-drug combinations given at MTD have been used before in pre-clinical 14 and clinical studies 12, 13 for BRAF V600E mutant tumours, showing clear therapeutic benefits, but such regimen have an associated cost of toxicity.…”
mentioning
confidence: 99%
“…For example, the Bayesian model highlighted the association between BRAF mutation in colorectal cancer and BRAF inhibitor response. Targeting BRAF signaling has recently been confirmed as a viable option for metastatic colorectal cancer cases with BRAF mutations 38 . In contrast, the Bayesian model excluded a suggestion from ANOVA of association between KRAS mutation with lenalidomide response in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…The likely reason for resistance is that targeting BRAF results in loss of negative feedback to the EGFR/RAS/RAF pathway, and that the additional EGFR signals can confound treatment with RAF inhibitors (42,43), possibly due to paradoxical activation of RAF due to the increased wild-type RAS-GTP (44)(45)(46). Subsequent studies have found BRAF mutant colorectal cancer can benefit from cotreatment with RAF, MEK, and EGFR inhibitors (47,48). It is still unknown whether the benefit from EGFR is solely due to inhibition of wild-type RAS or follows from the other pathways that EGFR can activate (49).…”
Section: Discussionmentioning
confidence: 99%